Javnomnenjska zaznava okoljske varnosti v Sloveniji - Malešič, Marjan (Teorija in praksa, 2023)
This study examines the undeniable connections between environmental and security issues in contemporary society, supported by scientific analyses. We specifically investigate the Slovenian public’s awareness of these connections through data analysis of SJM surveys (2020/3 and 2011/1) regarding attitudes to environmental problems. While we observe increasing sensitivity to environmental issues, public concern does not align with the severity of climate disasters, environmental terrorism, crime, civil-unrest-related violence, environmental refugees, and associated armed conflicts. Some of these phenomena have already impacted Slovenia’s security. Although the public acknowledges environmental problems, the consequences are insufficiently connected to daily lives, including security considerations.
Keywords: environment; environmental problems; environmental security; Javno mnenje; javnost; okolje; okoljska varnost; okoljski problemi; Okoljski vidik; perception; public; Slovensko javno mnenje; threats; Varnost; viri ogrožanja; zaznavanje